The Impact of K-Pop Idol on Brand Awareness, Hedonic Shopping Motivation, and Purchase Intention - Nabila Putri Andira; Raditya Adji Prasetyo; Artha Sejati Ananda (Universitas Prasetiya Mulya, 2023)
This research aims to know what factors are owned by endorsers that can influence consumer purchase decisions for the products offered by e-commerces. The secondary motivation of this research is to obtain empirical data on how influential the tactics made by e-commerce using K-Pop girlband/boyband are on purchase intention. The impact of celebrity worship factors is analyzed on data of Indonesia's K-Pop fans (n =100) using variance-based structural equation modeling and PLS-SEM process. The research results show a positive correlation between K-Pop brand ambassadors to raise brand awareness, hedonic shopping motivation towards Purchase Intention among K-Pop fans. This research contributes to the current knowledge-related online buying behavior in virtual retail formats and helps marketers in streamlining their focus in using K-pop figures to increase purchase decisions of targeted consumers.